Oxford Reading Tree: Survival adventure - Roderick Hunt (Karachi; Oxford University Press, 2012)
Part of a programme designed to teach young children to read, this is one of a group of fast-moving adventures featuring a host of characters, an information section of facts supported by colour photographs, and traditional tales selected from a wide range of cultures.
Keywords: junior